The Effect of Entrepreneurship Education on Student’s Entrepreneurship Intention in Vocational School - Ahmad Abdun Salam; Ibnu Siswanto; Mar’atus Sholikah (Universitas Jambi, Indonesia, 2021)
Entrepreneurship education is crucial for students to learn knowledge around entrepreneurial skills, attitudes, and stimulates entrepreneurial intentions. This study aims to analyze the influence of entrepreneurship education program on student’s entrepreneurship intention in vocational schools with gender as moderation. There were 198 respondents from seven vocational schools in Yogyakarta province participated in this quantitative study. The analysis technique used is PLS-SEM with the help of SmartPLS software. The result revealed that entrepreneurship education programs are positively related to student’s entrepreneurship inspiration and intention. Extracurricular entrepreneurship activity is also positively related to entrepreneurship education inspiration and student’s entrepreneurship intention. However, the result displayed that gender insignificantly moderates the relationship between entrepreneurship education program and student’s entrepreneurship intention in vocational high school. Besides, schools and teachers need to present learning programs and extracurricular activities that can inspire and intend to generate interest in student entrepreneurship in the future.